P018 Epidemiologic evidence that physicians with work-related mental ill-health are more likely to be reported by psychiatrists than by other physicians. (1st September 2016) - Zhou, Anli; Carder, Melanie; Hussey, Louise; Gittins, Matthew; Agius, Raymond
Abstract : Background: Work-Related Mental Ill-Health (WRMIH) in physicians could negatively affect wellbeing and subsequently impact patient care. However, physicians may choose to self-manage or bypass normal referral channels. Objectives: This study aimed to compare the incidence of WRMIH affecting physicians and selected control occupational groups, as reported by general practitioners (GPs) and specialists psychiatrists, occupational physicians (OPs), in order to investigate differential referral patterns for physicians. Methods: Data on medically reported incidence of WRMIH were collected prospectively between 2006–9 from GPs, psychiatrists and OPs reporting to The Health and Occupation Research (THOR) Network. For the GP and psychiatrist reporting schemes, incidence rates for physicians, nurses, teachers, corporate managers and protective service workers were calculated using Labour Force Survey for denominator data. For OPs, surveys of participating physicians provided denominators to analyse rates for physicians, nurses and teachers. Results: Average annual incidence rates expressed per 100, 000 by GPs and psychiatrists respectively were: physicians (308, 1050), teachers (1037, 140), nurses (889, 209), protective service workers (1428, 734) and corporate managers (427, 98). Average annual incidence rates expressed per 100, 000 for OP reporting were: 430 (physicians), 209 (teachers) and 670 (nurses). Psychiatrists reported a higher incidence of WRMIH in physicians compared to other occupations, whereas the GP reporting schemes reported higher incidences of WRMIH in other occupations (Chi squared test, p < 0.001). Estimated incidence rate ratios (IRR) demonstrate higher incidence rates of WRMIH in physicians are being reported by psychiatrists in comparison to OPs and GPs (IRR = 3.4:1 and 0.4:1 respectively). Conclusions: The distribution and incidence of cases reported by the different medical sources suggests a differential reporting pattern of WRMIH in physicians. Higher incidence rates of psychiatrist reported WRMIH in physicians could be due to stigmatisation, bypassing formal referral channels and disease severity.